A case of mitral valve plastics in the early postoperative period after orthotopic heart transplantation - B.M. Todurov; G.I. Kovtun; O.O. Samchuk; S.O. Sheludko; I.M. Kuzmich; O.M. Druzhyna; H.Yu. Melnyk (Кардіохірургія та інтервенційна кардіологія)
Today, heart transplantation is a gold standard treatment of the terminal chronic heart failure. Despite the constant improvement of the technique of this operation and the emergence of new protocols of immunosuppressive therapy, one of the main problems in the development of heart transplantation in Ukraine is a limited donor pool. The article presents a clinical case of successful orthotopic heart transplantation, followed by mitral valve repair in the early postoperative period. Our experience shows that mitral valve repair after orthotopic heart transplantation provides good results in the medium term, and this type of intervention can potentially expand the donor pool, thus increasing the number of heart transplants.